Bahasa Indonesia Interferensi Penekanan Bahasa Jawa terhadap Bahasa Indonesia: Studi Kasus di WhatsApp - Dora, Dora Hatika Pertiwi; Hindun, Hindun (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to determine the interference of Javanese language emphasis on Indonesian and to determine the factors that cause Javanese language interference to Indonesian. This study discusses the interference of Javanese emphasis on Indonesian and the factors that cause interference of Javanese emphasis on Indonesian through a case study via WhatsApp. This study examines language interference because Indonesia is a language community that has its own characteristics. From the language community, there is often a linguistic phenomenon in the form of language interference. This study uses a qualitative method by explaining the problem through information obtained from sources regarding the error in the emphasis of the Javanese language used. The data in this study are in the form of voice recordings containing the emphasis of Javanese on Indonesian. The instrument of this research used online interviews. Sources of data obtained from interviews using the technique of provocation to obtain information in the form of errors in the emphasis of the Javanese language on the Indonesian language. The data in this study were collected using the listening and note-taking technique. The results of this study indicate that there are several interferences in the emphasis of the Javanese language on Indonesian, which come from errors at the phonological level, morphological level errors, and errors at the semantic level. The interference of Javanese emphasis on Indonesian is caused by several factors, namely the social environment in which they live, the existence of bilingualism by speakers of the language, and improving language skills by speakers.